A Practical Approach to Newborn Screening for Severe Combined Immunodeficiency Using the T Cell Receptor Excision Circle Assay - Thakar, Monica S.; Hintermeyer, Mary K.; Gries, Miranda G.; Routes, John M.; Verbsky, James W. (Frontiers in Immunology, 2017)
Severe combined immunodeficiency (SCID) is a life threatening condition of newborns and infants caused by defects in genes involved in T cell development. Newborn screening (NBS) for SCID using the T cell receptor excision circle (TREC) assay began in Wisconsin in 2008, and has been adopted or is being implemented by all states in 2017. It is established that NBS using the TREC assay is extremely sensitive to detect SCID in the newborn period. Some controversies remain regarding how screening positives are handled by individual states, including when to perform confirmatory flow cytometry, what is the necessary diagnostic workup of patients, what infection prophylaxis measures should be taken, and when hematopoietic stem cell transplantation (HSCT) should take place. In addition, the TREC assay detects infants with T cell lymphopenia (TCL) who are not severe enough to be considered SCID; management of these infants is also evolving.